Power Trade in South Asia: Developing A Framework Based on Case Studies of Power Trading Arrangements in Europe and Asia. (September 2021) - Chauhan, Priyanshi
South Asia is the fastest growing region in the world and is experiencing increasing demand for energy. As a result, countries are witnessing an excessive reliance on fuel imports, making themselves vulnerable to external price volatility and compromising on energy security. Power trade in South Asia can meet the challenge of increasing energy demand owing to complementarities in resource endowments and peak demand. Power trade in South Asia has increased over the years but is below potential. However, there are various challenges due to lack of institutional structures and frameworks for developing regional power trade models. The examples of power integration models in Europe, that is, the Nordic power market, and in Southeast Asia, that is, power trade in the Greater Mekong Subregion (GMS), can provide useful lessons and international best practices for regional power trade to be replicated in the South Asian context. Based on this, the objective of this article is to evaluate the existing power trading mechanisms in South Asia, highlight the challenges to regional energy cooperation, outline the necessary instruments and catalysts to promote regional power trade in South Asia based on the case study of successful power trading arrangements, including the Nordic power market in Europe and the Greater Mekong Subregion (GMS) in Southeast Asia, draw on their experiences to identify key mechanisms and develop a template for greater regional cooperation in electricity in South Asia.